Social Inclusion Challenges for Different Society Groups in Latvia - Sloka, Biruta; Tora, Ginta; Buligina, Ilze; Dzelme, Juris (Journal of Service, Innovation and Sustainable Development, 2021)
Latvia has been receiving critical remarks from international institutions in regard to high level of social inequality of various groups in the society. Statistical data indicate that the society of Latvia has to address serious challenges in social inclusion, including several aspects in health care. The aim of the paper is to propose possible solutions for social inclusion of different society groups, especially in relation to health care aspects and including application of life-long-learning for health care for several society groups. Research approach to the problem: analysis of data obtained in representative survey 9280 respondents: health condition self-evaluation analysis by regions, by gender, by administrative territory, by age groups, by economic activity and by education level, as well as survey of social service representatives in municipalities in Latvia. For a more thorough data analysis (used evaluation scale 1-5) indicators of descriptive statistics are applied; cross – tabulations; testing of statistical hypotheses with t-test and analysis of variance – ANOVA; correlation analysis. Research results indicate that the use of more diverse approaches of social marketing and life-long-education programs to inform and educate various groups of society on health care aspects might produce beneficial effects to decrease social inequality of different society groups.
Keywords: Social inclusion; health condition; self-evaluation; material deprivation; Research Subject Categories::SOCIAL SCIENCES::Business and economics